Immotility as resilience? A key consideration for transport policy and research. Issue 1 (2nd January 2017) - Ferreira, Antonio; Bertolini, Luca; Næss, Petter
Abstract: Contemporary transport systems lack resilience. They are prone to congestion, vulnerable to multiple threats, constitute a great financial burden and are environmentally unsustainable. Research and policies have been developed aimed at solving these problems by means of improving transport technologies and governance; however, success has been limited. This paper asks whether resilience can be increased also by means of promoting localism, slowness and stillness, or what we synthetically term "immotility". This is a valuable enterprise because in the recent past the focus has been on the highly mobile and the global. The highlighted knowledge gap is problematic because it reduces the perceived value of development models which are not based on high-speed, long distance and high-frequency mobility.